Investigating the effectiveness of a smart mental health intervention (inMind) for stress reduction during pharmacological treatment for mild to moderate major depressive disorders: Study protocol for a randomized control trial - Kim, Junhyung; Shin, Cheolmin; Han, Kyu-Man; Lee, Moon-Soo; Jeong, Hyun-Ghang; Pae, Chi-Un; Patkar, Ashwin A.; Masand, Prakash M.; Han, Changsu (Frontiers in Psychiatry, 2023)
Background: Although psychological interventions for stress relief, such as cognitive behavioral therapy (CBT) and mindfulness-based stress reduction (MBSR), have been developed, they have not been widely used in treating depression. The use of mobile devices can increase the possibility of actual use by integrating interventions and reducing the difficulty and cost burden of treatment application. This study aims to determine whether “inMind,” an integrated mobile application for stress reduction, developed for the general population, decreases stress for patients with mild to moderate major depressive disorder during the pharmacological treatment period. Methods: This study is a single-blind, multicenter, randomized, controlled crossover trial. The App, developed in South Korea, provides integrated interventions for stress reduction for the general population through three modules based on mindfulness-based stress reduction, cognitive behavior therapy, and relaxation sounds that are known to be effective in stress reduction (“meditation,” “cognitive approach,” and “relaxation sounds,” respectively). Participants (n = 215) recruited via medical practitioner referral will be randomized to an App first group (fAPP) or a wait list crossover group (dAPP). The study will be conducted over eight weeks; the fAPP group will use the App for the first four weeks and the dAPP group for the next four weeks. During all study periods, participants will receive their usual pharmacological treatment. The Depression Anxiety Stress Scale-21 is the primary outcome measure. The analysis will employ repeated measurements using a mixed-model approach. Discussion: The App can potentially be an important addition to depression treatment because of its applicability and the comprehensive nature of the interventions that covers diverse stress-relieving models.